MANUSIA TIDAK DAPAT TIDAK BERKOMUNIKASI - Parapat, Nelson Halong (Jurnal Insani, 2019)
This paper gives us an understanding that we cannot not communicate. In our lives, whether intentionally or unintentionally, we have communicated with the people around us from the moment we are born until we die. Communication is the process of understanding each other's meaning between two fellow humans. Communication occurs when a person's behaviour has been interpreted by others to give meaning to that person's behaviour. That is, we are considered to have communicated if our behavior has been interpreted by others even though we do not intend to convey any message to him. Thus, we cannot avoid communication.The thought that we cannot not communicate can be understood because in communication there are principles of communication, namely: the core content of communication is meaning; meaning is the result of interpretation of behaviour; communication has occurred if someone has interpreted the behaviour of others, both verbal behaviour and nonverbal behaviour, regardless of whether the person is aware or not aware of it; and we cannot control others to interpret or not interpret our behaviour.Communication behaviour can be unintentional or intentional behaviour. Deliberation is not a requirement for communication. Every behavior has communication potential. In everyday life, in the midst of communication that we consciously do, often tucked into communication behaviour that we are not aware of or unintentional.